Nuclear emulsion measuring the prompt fission neutron spectrum of 238U induced by 2.8 MeV neutrons. (August 2016) - Wen, Weiping; Li, Guangwu; Wang, Hongkai
Abstract: The spectra of neutrons emitted in fission of 238 U induced by 2.8 MeV neutrons were measured by N-4 nuclear emulsion. Details like the experimental layout and conditions, and the track data reading, processing and correction were described. Also the energy-range relation of recoil protons among the N-4 nuclear emulsion was derived by Monte Carlo simulation and fitting method for the first time. The experimental results were presented as relative yields and were compared to the calculations using Maxwell and Watt models. The results were approximately the same as the theoretical PFNS, especially for those 3–6 MeV and 11–14 MeV outgoing neutrons, and the availability of nuclear emulsion measurement in the high-energy part of PFNS was proved.